Healing, Antioxidant and Cytoprotective Properties of Indigofera truxillensis in Different Models of Gastric Ulcer in Rats - Luiz-Ferreira, Anderson; Cola, Maira; Barbastefano, Victor; de-Faria, Felipe Meira; de Almeida, Ana Beatriz A.; Farias-Silva, Elisangela; Calvo, Tamara Regina [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP]; Vilegas, Wagner [UNESP]; Souza-Brito, Alba Regina M. (Mdpi Ag, 2012)
The present study evaluated the antiulcerogenic activity and mechanisms of the aqueous (AqF 100 mg/kg) and ethyl acetate (AcF 50 mg/kg) fractions from Indigofera truxillensis leaves. This dose was selected to assess its activity on ulcer healing and its action on gastric acid and mucus secretion, prostaglandin production and antioxidant enzyme activity (superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and glutathione reductase (GSH-Rd)). Gastric ulcer was induced by absolute ethanol. Antisecretory action, mucus and prostaglandin production, healing and antioxidant enzyme activities were evaluated for both fractions. AqF and AcF significantly inhibited the gastric mucosal damage caused by ethanol. This effect was statistically significant at 100 and 50 mg/kg compared with the vehicle. Neither fraction interfered with gastric secretion. AcF increased the PGE(2) production, and both fractions increased mucus production. L-NAME did not alter the gastroprotection exerted by the fractions, but N-ethylmaleimide attenuated only AcF. In the ischemia/reperfusion model both fractions inhibited the mucosal damage. AcF increased SOD, GSH-Px and GSH-Rd activity, but AqF increased only SOD and GSH-Px. In the acetic acid-induced ulcer model AcF only accelerated ulcer healing. These results showed that Indigofera truxillensis acted as a gastroprotective agent, stimulating protective factors and antioxidants enzymes.
Keywords: Indigofera truxillensis; gastric ulcer; medicinal plants; antioxidant enzymes